EXISTANCE OF SPATIAL SEGREGATION IN GUNUNG ANYAR JAYA UTARA HOUSING IN SURABAYA - Merisa Kurniasari (Journal of Architecture&ENVIRONMENT, 2019)
Spatial segregation can trigger the presence of social problems such as marginalization of vulnerable economies, criminality, and the loss of social sensitivity. Spatial segregation is characterized by the formation of space barriers derived from the manifestation of the diversity of socio-economic conditions. This research is a simple research with qualitative approach which is done in GunungAnyar Jaya Utara housinginSurabaya based on protest that is sent by societybecause of limitation of space accessibility by developer. This study also identified the formation of Neighborhood from the housing of GunungAnyar Jaya Utara. The result of the research shows that there is an insulation that causes the movement of activity of the local residentsto be limited.